Design of radar display of Indonesian airspace monitoring application - Sulistyaningsih Sulistyaningsih; Yussi Perdana Saputera; Mashury Wahab; Yudi Yulius Maulana (Universitas Ahmad Dahlan, 2019)
In this research, the design and manufacture of radar display software using Plan Position Indicator (PPI) format for air surveillance radar application are presented. The PPI display shows interpretations of echo detections of radar signal reflected from the flying objects/targets. The detection results will be displayed on a circular 360ᵒ area, where the radar position is at the center. System configuration is done via interface from the display, by adjusting the level of transmit signal, by setting the gain for threshold, and by enabling moving target indicator (MTI) mode. The MTI mode only displays moving objects and no non-moving objects are shown such as mountains and buildings. Based on the results of this research, the PPI display shows the targets on the display according to its position, some desired targets can also be tracked, information on target, GPS location, target ID, required parameters, and some settings. The radar display fulfills all the required capabilities for air surveillance radar.